2007
DOI: 10.1523/jneurosci.3404-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome and Metabolic Gene Signature of Protoplasmic Astrocytes in the Adult Murine Cortex

Abstract: Protoplasmic astrocytes are critically important to energy metabolism in the CNS. Our current understanding of the metabolic interactions between neurons and glia is based on studies using cultured cells, from which mainly inferential conclusions have been drawn as to the relative roles of neurons and glia in brain metabolism. In this study, we used functional genomics to establish the relative compartmentalization of neuronal and astrocytic metabolic pathways in the adult brain. To this end, fluorescence-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
417
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(461 citation statements)
references
References 52 publications
(65 reference statements)
30
417
0
9
Order By: Relevance
“…The astrocytic filopodial processes that surround and interact with synaptic structures contain mitochondria (Lovatt et al, 2007;Pardo et al, 2011;Lavialle et al, 2011) and have the potential to oxidize glucose, glycogen, and glutamate during activation. If brain activation stimulated only glycolysis in astrocytes, it would be reasonable to assign the ATP derived from this pathway toward the energetics of glutamate uptake.…”
Section: Brain Activation In Vivo Activates Glycogenolysis and Oxidatmentioning
confidence: 99%
“…The astrocytic filopodial processes that surround and interact with synaptic structures contain mitochondria (Lovatt et al, 2007;Pardo et al, 2011;Lavialle et al, 2011) and have the potential to oxidize glucose, glycogen, and glutamate during activation. If brain activation stimulated only glycolysis in astrocytes, it would be reasonable to assign the ATP derived from this pathway toward the energetics of glutamate uptake.…”
Section: Brain Activation In Vivo Activates Glycogenolysis and Oxidatmentioning
confidence: 99%
“…In contrast to the mixed distribution of GPR37, GPR37L1 is highly expressed in astrocytes, with in situ hybridization revealing greatest density of GPR37L1 within the Bergmann glia of the cerebellum (Valdenaire et al, 1998). Microarray studies reported more than 100 times higher expression of GPR37L1 in rat and mice astrocytes compared with neurons (Cahoy et al, 2008; Lovatt et al, 2007; Zhang et al, 2014). GPR37L1 is also expressed in oligodendrocytes (Zhang et al, 2014).…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…Primary cultures of astrocytes, which provide a seductive experimental simplicity, are not reliable indicators of the properties of astrocytes and how they behave in situ (Kimelberg, 1995;Kimelberg et al, 1997;Kimelberg, 2001;Lovatt et al, 2007;Cahoy et al, 2008). These alternative paths are (1) release by reversal of excitatory amino acid (EAA) transporters, which is only likely to occur under pathological conditions, (2) swelling activated anion channels and also hemi-channels, and (3) P2X receptors for ATP.…”
Section: Are There Widespread Consequences Of Alterations In Astrocytmentioning
confidence: 99%
“…Otherwise the energy requirements at the process ends would have to be met by glycolysis, which is much less efficient. However, a recent paper in which GFAP promoter-driven GFP was used to identify small astrocyte perisynaptic end-feet found that the number of mitochondria in the end-feet was either as great or greater than other profiles in the surrounding neuropil (Lovatt et al, 2007). However, Chao et al (2002) using electron microscopy and S100-immunoreactivity to identify the processes have noted previously that the fine lamellae and filipodia are devoid of organelles, unlike the astrocytic cell body and processes.…”
Section: A General Support Role For Astrocytesmentioning
confidence: 99%